Characteristics of users and implications for the use of complementary and alternative medicine in Ghanaian cancer patients undergoing radiotherapy and chemotherapy: a cross- sectional study - Yarney, J.; Donkor, A.; Opoku, S.Y.; Yarney, L.; Agyeman-Duah, I.; Abakah, A.C.; Asampong, E. (My University, 2013)
Abstract Background There is widespread use of Complementary and Alternative Medicine (CAM) in Ghana, driven by cultural consideration and paradigm to disease causation. Whether there is concurrent use of conventional medicine and CAM in cancer patients is unknown. This study investigates the prevalence, pattern and predictors of CAM use in cancer patients. Overlapping toxicity, sources of information, and whether users inform their doctor about CAM use is examined. Method Cross-sectional study using a questionnaire administered to cancer patients, who were receiving radiotherapy and or chemotherapy or had recently completed treatment at a single institution was used. Results Ninety eight patients participated in the study with a mean age of 55.5 (18–89), made up of 51% females. Married individuals formed 56% of the respondents, whilst 49% had either secondary or tertiary education. Head and neck cancer patients were 15.3%, breast (21.4%), abdomen/pelvic cancers constituted (52%).Seventy seven (78.6%) patients received radiotherapy only, 16.3% received radiation and chemotherapy and 5.3% had chemotherapy only.Ninety five patients were diagnosed of cancer within the past 24 months,73.5% were CAM users as follows; massage(66.3%), herbal(59.2%), mega vitamins(55.1%), Chinese medicine(53.1%),and prayer(42.9%). Sixty eight percent were treated with curative intent. Overlapping toxicity was reported. Majority (83.3%) of users had not informed their doctor about CAM use.On univariate analysis, female (p=0.004) and palliative patients, p=0.032 were more likely to be CAM users. Multivariate analysis identified female (p<0.01), as significant for use, whilst head and neck site was significant for non use (p<0.028). Young, married and highly educated individuals are more likely to use CAM.Friends and Media are the main sources of information on CAM. There was increase in CAM use after the diagnosis of cancer mainly for Chinese Medicine and vitamins. Conclusion There is high CAM usage among Cancer patients, comparable to use in the general population, there is concurrent use of CAM and conventional medicine with reported overlapping toxicity but without informing Oncologist about use. Women and palliative patients are more likely to use CAM. Doctor patient communication on herbal-radiotherapy and drug treatment interaction needs to be strengthened. Standardization and regulation of CAM use is paramount.